Feeding frequency on the growth and production of endemic near-threatened Ompok pabda (Hamilton 1822) in pond setup - Islam, Md Ashraful; Samad, Md Abdus; Paul, Dipankar; Asif, Abdulla Al; Hossain, Amir (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
Growth and production of near threatened Ompok pabda (Hamilton) were examined at different feeding frequencies in the present study. The experiment was conducted for four months in three earthen ponds from 1st April to 31st July 2018 at Tanore Upazila in Rajshahi district, Bangladesh. The experiment was performed using pabda, (Ompok pabda) fingerling (average) to study the effect of feeding frequency on growth performance. The study carried out considering three treatments, namely T1, T2, and T3; while the feeding frequency was two times per day in treatment T1, three times per day in treatment T2, and four times per day in treatment T3. Fish were fed considering three-stage of life span; these were fingerling stage, early growing stage, and growing stage. In the fry stage, the fishes were fed 20% feed, in the fingerlings stage the fish were fed 10% feed and in the growing stage, the fish were fed 8% feed of the body weight. The mean water temperature ranged between 27.13±2.10 and 27.29±2.16 °C among treatments, while water transparency ranged between 31.91±1.58 and 29.96±1.84 cm. pH ranged between 7.62±0.14 and 7.70±0.19; while the mean dissolved oxygen was ranged between 5.35±0.11 and 5.56±0.14 among treatments. The final weight gain was found to be highest (56.36±0.01) in the treatment T2 and lowest (38.23±0.01) in the treatment T3. The SGR value was higher (3.94±0.01) in the treatments T2 followed by treatments T1 and T3. Net weight gain was significantly (p<0.05) higher in feeding frequency three (56.36±0.1), followed by feeding frequency four (38.23±0.1) and feeding frequency two (40.67±0.73). The FCR value ranged between 1.90 and 2.87 among treatments. The growth performance and specific growth rate were significantly (p<0.05) higher in feeding frequency three. The highest (4049.1±0.1 kg/ha/120 days) production was observed in T2. Best cost benefit ratio was gained in treatment T2. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (2), 89-102